Tethered aminohydroxylation: dramatic improvements to the process. - Donohoe, T; Bataille, C; Gattrell, W; Kloesges, J; Rossignol, E (2007)
[reaction: see text] Changing the identity of the N leaving group on a hydroxylamine-based reoxidant gives a dramatic improvement to the tethered aminohydroxylation reaction. Using OCOC6F5 as a leaving group means that only 1 mol % of osmium is required and yields as high as 98% can be obtained. Acyclic homoallylic alcohols were substrates considered too unreactive for effective use in the tethered aminohydroxylation reaction; improved reaction conditions mean that they have now become viable substrates for oxidation.